This Prison Where I Live - Bloomstein, Rex (Rex Entertainment Ltd. ; Yo Man Media, 2010)
Duration: 01:30:00 An intimate portrait of two comedians: Maung Thura, better known as Zarganar, one of Burma’s greatest living comedian, relentlessly victimised and imprisoned by the Burmese military junta, and Michael Mittermeier, one of Germany’s leading stand up comedians. Two men joined by comedy and separated by repression.